KEPEMIMPINAN, MOTIVASI KERJA, DAN KOMPETENSI: PENGARUHNYA TERHADAP KINERJA KARYAWAN DI KJPP ADITYA ISKANDAR DAN REKAN : LEADERSHIP, WORK MOTIVATION, AND COMPETENCE: THEIR EFFECT ON EMPLOYEE PERFORMANCE AT KJPP ADITYA ISKANDAR AND PARTNERS - Nadirah, Nadirah; Suhartono, Suhartono; Ridho Jun , Ridho Jun; Prasetyo, Prasetyo (Visioner : Jurnal Manajemen dan Bisnis, 2024)
This study intended in assessing the Leadership (X1), Work Motivation (X2), and Competency (X3) impact towards Performance (Y) from the perspective of employees at KJPP Aditya Iskandar and Partners, both individually and collectively. Data for this research were drawn from employee performance reports spanning six years, from 2018 to 2023. This quantitative study involved all employees from the KJPP technical and operational division, totaling 63 respondents. The data collection employed Non- Random Sampling, specifically judgmental sampling, and was conducted using a questionnaire. Analysis performed by using multiple linear regression. The findings imply that X1 and X2 have an insignificant impact towards Y. X3 meanwhile exerts positive significant influence. Collectively, X1, X2, and X3 positively and significantly impact Y.